Faktor Risiko Tradisional Kardiovaskular terhadap Kejadian Disfungsi Ereksi pada Pasien Penyakit Jantung Koroner - Heri Hernawan; Irsad Andi Arso; Erika Maharani (The Indonesian Heart Association, 2016)
Background: Erectile Dysfunction (ED) is defined as the inability to achieve or maintain an erection sufficient to permit satisfactory sexual intercourse. Erectile dysfunction affects more than 150 million men worldwide and impairs psychological well-being and personal relationships, hence quality of life. Recent studies have shown that ED is present in 42% to 76% of men with coronary artery disease (CAD). Epidemiological study showed clearly role of traditional cardiovascular risk factors such as diabetes, hypertension, dyslipidemia and smoking in CAD. Erectile dysfunction and vascular diseases share a similar risk factors and pathogenic involvement of nitric oxide (NO)-pathway leading to impairment of endothelium-dependent vasodilatation (early phase) and structural vascular abnormalities (late phase). This study was conducted to determine whether the stable CAD patients who have traditional cardiovascular risk factors has a higher risk for ED compared with stable CAD patients without traditional cardiovascular risk factors.Methods: We performed an age matched-paired case control study. Men with CAD documented by angiography were evaluated for ED. Erectile function was assessed by a 5-item version of the International Index of Erectile Function (IIEF-5). Traditional cardiovascular risk factors such as diabetes, hypertension, dyslipidemia and cigarette smoking were assesed. Depression and anxiety were screened using Indonesian version of Hospital Anxiety and Depression Scale (HADS). Basic demographic and other variables were also collected.Results: This study evaluated 127 men, 96.8% of them had traditional cardiovascular risk factors, 25.2% had diabetes mellitus, 77.2% had dyslipidemia, 55.9% had hypertension and 64.6% were smoker. Traditional cardiovascular risk factors was strongly associated with ED (OR=10.67 [1.25-232.83]). ED was independently associated with diabetes mellitus (OR=4.17 [1.14-15.24]), hypertension (OR=2.64 [1.07-6.49]) and cigarette smoking (OR=2.26 [1.01-5.75]).Conclusion: CAD patients with traditional cardiovascular risk factor had more risk for developing ED than those with no traditional cardiovascular risk factor.